Els adjectius expressius del català - Xavier Villalba (Catalonia)
This article offers the first complete formal description of the pragmatic and syntactic properties of expressive adjectives in Catalan, such as fotut -da (Ets un fotut comediant «You're a fucking comedian») or puto -a (Això és una puta mentida «That's a fucking lie»). Regarding interpretation, expressive adjectives are characterized by incorporating an emotional content associated with the speaker's perspective that does not have an impact on denotative semantics, but on an independent expressive level. Regarding syntax, unlike qualifying adjectives, expressive adjectives are not usually quantified, tend to appear in prenominal position and are combined to obtain intensive effects. Overall, the study of these often-neglected elements gives us an important insight into the connections between semantics, pragmatics and syntax and also into the way in which lexical elements develop expressive meanings.